Bioindicator nematodes in relation to an abiotic stress gradient in soils influenced by mining (Scientia Agropecuaria, 2023)
The attributes of nematodes are presented as valuable tools for determining the quality of soil, especially that of mining companies. The aim of this study was to evaluate the behavior of nematodes against a stress gradient in a rainy season and a dry season in soils influenced by mining. Thus, field sampling was carried out over 100 m2 in triplicate for four types of soils classified according to their uses (pasture, maize cultivation, fig cultivation, and eucalyptus cultivation), and these areas were located on the periphery (500 to 1500 m) of the Ollachea mining community of Puno in Peru; subsequently, the samples were processed in the laboratory to determine edaphic, agrochemical, heavy metal, and microbiological parameters and identify the nematodes. The abiotic stress gradient was determined by a principal component analysis; and through a canonical correlation analysis, the relationships between the abiotic stress gradient and the nematodes were determined. Canonical correlation analysis showed that there were significant correlations: in the rainy season, Helicotylenchus and vanadium (r = 0.99), Globodera and titanium (r = 0.97), and Tylenchus and lead (r = 0.96); in the dry season: Meloidogyne and vanadium (r = 0.99), and Hemicycliophora and lead (r = 0.91). In conclusion, the abiotic stress gradient had a high correlation with bacterivorous, fungivorous, and phytoparasitic nematodes and a low correlation with omnivorous and predatory nematodes, showing the bioindicator capacity of nematodes in relation to stress parameters that impact soil quality.
Keywords: edaphic ecosystems; edaphic nematodes; functional groups; physicochemical parameters; soil health